Social Capital in Policy : Putnamian's perspective on Banyuwangi Ethno Carnival - Khanifatul Mukaromah; Priyatno Harsasto (Journal of Politic and Government Studies, 2020)
The success of Government Policy is not only based on the role of localgovernment alone, but is a collaborative collaboration between various stakeholders and the community . Full community involvement influences thesuccess of government programs . Through annual activities, namely theBanyuwangi Ethno Carnival with the aim to encourage the Banyuwangi Regencycommunity initiatives to harmonize and form a collaboration between the governmentand the community or cultural groups. In this study presents evidence of the strengthof social capital in an activity through basic ideas by Robert Putnam. The researchmethod used is descriptive qualitative with data collection techniques in the form ofinterviews and documentation. The data obtained were then analyzed usingTriangulation Methods, Theory and Data Sources . The findings of this study are through the tradition of mutual cooperation to build Banyuwangi Ethno Carnival involving the role of various parties in theimplementation of the event . Society, culture and art studio work together to buildrelationships in accordance with their capacity. To facilitate the flow of coordination,the Banyuwangi District Culture Office provides space for the community toparticipate and be active as a committee or technical implementer of BEC events. Thisis based on the participation of Cultural Groups in BEC . The conclusion that can be drawn from this study is that the first Social Capital starts from the community through three forms of social capital, namelyBonding , Bridging and Linking which are forms of community cooperation throughvarious parties in it . In the form of bounding is a form of interaction or communitycollaboration with local group. Second, the form of bridging is the interaction orcollaboration between the community and the community, community or othercultural groups. Third in the form of linking is the interaction or collaborationbetween the community and formal institutions such as the government. Based on theconclusions, the suggestions that can be given are that the implementation of culturalfestival activities through Banyuwangi Ethno Carnival is expected not only during theterm of office of Abdullah Azwar Anas, but will continue to be a continued annualactivity . Keywords: Social Capital, Mutual Cooperation, Policy , Community Participation